2013
DOI: 10.1371/journal.pone.0053238
|View full text |Cite
|
Sign up to set email alerts
|

SOX4 Mediates TGF-β-Induced Expression of Mesenchymal Markers during Mammary Cell Epithelial to Mesenchymal Transition

Abstract: The epithelial to mensenchymal transition program regulates various aspects of embryonic development and tissue homeostasis, but aberrant activation of this pathway in cancer contributes to tumor progression and metastasis. TGF-β potently induces an epithelial to mensenchymal transition in cancers of epithelial origin by inducing transcriptional changes mediated by several key transcription factors. Here, we identify the developmental transcription factor SOX4 as a transcriptional target of TGF-β in immortaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 43 publications
(56 reference statements)
3
83
0
Order By: Relevance
“…That the computational model at the core of ISMARA, i.e., motif activity response analysis, is a powerful method for reconstructing regulatory interactions from high-throughput data has already been demonstrated, not only in its original application (The FANTOM Consortium et al 2009), but in a substantial number of recent studies across a wide range of mammalian systems (Summers et al 2010;Aceto et al 2012;Arner et al 2012;Arnold et al 2012b;The FANTOM Consortium et al 2012;Hasegawa et al 2012;Pérez-Schindler et al 2012;Eisele et al 2013;Meier-Abt et al 2013;Tiwari et al 2013a,b;Vervoort et al 2013). In each of these studies, MARA successfully inferred key regulators and their regulatory interactions ab initio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the computational model at the core of ISMARA, i.e., motif activity response analysis, is a powerful method for reconstructing regulatory interactions from high-throughput data has already been demonstrated, not only in its original application (The FANTOM Consortium et al 2009), but in a substantial number of recent studies across a wide range of mammalian systems (Summers et al 2010;Aceto et al 2012;Arner et al 2012;Arnold et al 2012b;The FANTOM Consortium et al 2012;Hasegawa et al 2012;Pérez-Schindler et al 2012;Eisele et al 2013;Meier-Abt et al 2013;Tiwari et al 2013a,b;Vervoort et al 2013). In each of these studies, MARA successfully inferred key regulators and their regulatory interactions ab initio.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas many laboratories are now routinely producing high-throughput data sets, and methodologies for analyzing such data have been described in the literature, the vast majority of groups that produce data have to develop collaborations with expert computational groups to apply these methods. Indeed, in recent years MARA has been applied to a large range of mammalian systems studied by various experimental collaborators and experimentally validated predicted regulatory circuitry in these systems (Summers et al 2010;Aceto et al 2012;Arner et al 2012;Hasegawa et al 2012;Pérez-Schindler et al 2012;Suzuki et al 2012;Eisele et al 2013;Meier-Abt et al 2013;Tiwari et al 2013a,b;Vervoort et al 2013). Although these studies further validated the power of the method, they required a considerable investment of time and effort for the analysis of each new data set.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…SOX4 and SOX9 are known regulators of these pathways in cancer and development (Bhattaram et al, 2010;Delous et al, 2012;Kuwahara et al, 2012;Manfroid et al, 2012;Moreno, 2010;Scharer et al, 2009;Song et al, 2013;Vervoort et al, 2013), raising the possibility that SOX factors control biliary development by modulating the response to intercellular signaling. To -14 -address this hypothesis, we investigated the expression of signaling markers in SOX factor-deficient livers.…”
Section: Sox4 and Sox9 Control Signaling Pathways Involved In Biliarymentioning
confidence: 99%
“…24,25 In addition, SOX4 was shown to regulate several key signaling pathways in cancer cells such as the Wnt pathway, Notch1 pathway, and P53 pathway. 26,27 Of note, SOX4 could serve as a master mediator in EMT process by regulating EMT marker, 28,29 which is a critical step in tumor progression and metastasis. 30 In this study, SOX4 was identified as a direct target of miR-25 by a luciferase reporter assay, quantitative reverse transcription polymerase chain reaction (qRT-PCR), and western blot.…”
Section: Discussionmentioning
confidence: 99%